2004
DOI: 10.1002/polb.10757
|View full text |Cite
|
Sign up to set email alerts
|

Molecular relaxation of isotactic polystyrene: Real‐time dielectric spectroscopy and X‐ray scattering studies*

Abstract: The molecular relaxation processes and structure of isotactic polystyrene (iPS) films were investigated with real-time dielectric spectroscopy and simultaneous wide-and small-angle X-ray scattering. The purpose of this work was to explore the restrictions imposed on molecular mobility in the vicinity of the ␣ relaxation (glass transition) for crystallized iPS. Isothermal cold crystallization at temperatures of T c ϭ 140 or 170°C resulted in a sigmoidal increase of crystallinity with crystallization time. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 40 publications
5
58
2
Order By: Relevance
“…The authors 56,58 consider it as an indication for the existence of upper glass transition point (T g U ), where RAP relaxation occurs. 12,[43][44][45] The authors 57 do not agree with this. On their opinion, this relaxation process is connected with the transition of ordered regions into the condis-crystal state, and its molecular mechanism is suggested.…”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations
“…The authors 56,58 consider it as an indication for the existence of upper glass transition point (T g U ), where RAP relaxation occurs. 12,[43][44][45] The authors 57 do not agree with this. On their opinion, this relaxation process is connected with the transition of ordered regions into the condis-crystal state, and its molecular mechanism is suggested.…”
Section: Resultsmentioning
confidence: 46%
“…Therefore, the increase in crystallinity usually results in the increase of the relaxation time for the a a -transition [62][63][64] and of the glass transition temperature. 45 Moreover, for the copolymer with higher HFP content the dimensions of the amorphous space between adjacent lamellae packed into stacks increase from 7.6 to 14.6 nm. 47 By the example of isotactic polystyrene it was shown that this must lead to the decrease of relaxation time of the transition under consideration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data such as those in Figure 4(c) show that the oriented segments relax at a higher temperature (T g $ 80-90 8C) than the unoriented segments (T g $ 30-50 8C). 62 The higher T g fraction is called the rigid amorphous fraction (RAF), [63][64][65] and the lower T g fraction corresponds to the conventional amorphous fraction. It is sometimes thought that the RAF is at the fold surface of the lamellae.…”
Section: Glass Transitionmentioning
confidence: 99%